2022
DOI: 10.3389/fnut.2022.854868
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Some Varieties of Apricot Present in the Vesuvius Area, Southern Italy

Abstract: The witnesses of the millenary history of Campania felix in southern Italy highlighted that several fruit and vegetables cultivated in such territory could potentially be a treasure trove of important health elements. Our work evaluated the content of β-carotene, ascorbic acid, and total phenolics and the antioxidant activity of ten typical varieties of apricots cultivated in the Vesuvius area in the Campania region. The total polyphenols varied between 10.24 and 34.04 mg/100 g of a fresh sample. The amount of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 63 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…The dried product becomes less thermolabile ascorbic acid due to the large increase in drying agent temperature. Other studies found comparable results for drying apples [72][73][74].…”
Section: Ascorbic Acid Content Of Apricotsmentioning
confidence: 58%
See 1 more Smart Citation
“…The dried product becomes less thermolabile ascorbic acid due to the large increase in drying agent temperature. Other studies found comparable results for drying apples [72][73][74].…”
Section: Ascorbic Acid Content Of Apricotsmentioning
confidence: 58%
“…The amount of thermolabile ascorbic acid in the dried product decreases as a result of the drying agent's temperature being significantly raised. Similar findings for drying apples, pears, peppers, etc., were found in other studies [70][71][72][73][74]. The Wojdyo et al study's [70] drying methods and parameters had a substantial impact on the red fresh apple's physical, chemical, and particularly bioactive qualities.…”
Section: Ascorbic Acid Content Of Applesmentioning
confidence: 64%
“…The genus Prunus is widely known for its delicious fruits. The apricot fruit is characterized with not only a distinct flavor and odor but also a variety of health-enhancing compounds like phenolic compounds and carotenoids [2]. Worldwide, all cultivated apricots originate from only one species-the Prunus armeniaca L., and, according to authors, apricot varieties are categorized into four eco-geographical groups, namely Central Asia, Europe, Iran-Caucasus, and Dzhungar-Zailing [3].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is generally believed that landraces are a source of trait variation for local adaptation and resilience to extreme climate conditions [8,9]. Landraces of fruit trees are also appreciated because they provide fruits with superior aroma and taste [10,11] and this is also related to the fruiting habit of the variety [12]. It is likely that this adaptive diversity is not largely considered in apricot breeding programs, currently carried out in a limited number of nations.…”
Section: Introductionmentioning
confidence: 99%